MEANINGS LOST IN TRANSLATION BETWEEN ITALY AND LATIN AMERICA: “YO NO TE PIDO LA LUNA” AND “NO ME AMES” - Di Somma, Teresa; Messina, Marcello (TROPOS: COMUNICAÇÃO, SOCIEDADE E CULTURA (ISSN: 2358-212X), 2018)
In this paper we seek to investigate the loss of emancipatory meanings undergone by the lyrics of two Italian songs upon their translation/adaptation into Castilian Spanish for Latin American and Spanish audiences. In particular, we compare [1] Fiordaliso’s “Non voglio mica la luna” (1984), with its Mexican cover “Yo no te pido la luna” by Daniela Romo (1984); and [2] Aleandro Baldi’s “Non amarmi” (1992), with Jennifer Lopez and Marc Anthony’s US version “No me ames” (1999). We observe that, while the former turns from a proud assertion of female sexuality and independence into a plea for pure and unconditional love in the process of translation and adaptation, the latter tackles important issues related to blindness and disability in the original, which are totally absent from the cover. After unveiling these fundamental differences, we interrogate the intricate web of market forces and power relations at stake in these processes.